Influencia del programa de estilos de aprendizaje basado en la "PROGRAMACIÓN NEUROLINGÜÍSTICA" (P.N.L.), para el aprendizaje significativo del idioma inglés en alumnos del 3 er grado del nivel secundario de la I.E. Juan Jiménez Pimentel - Tarapoto - 2008 - Reynoso Escalante, Kathia Milagros (2010)
Since we were college students we have been very interested in the situation and problems teachers have to face in our context, Tarapoto, PERÚ. So we decided to contribute to the solution of these problems. We ask for the opinions and suggestions of the teachers who teach English at the "Juan Jimenez Pimentel" School. We also watched sorne English classes in the same school. Our aim was to elaborate and apply a program based on Neurolinguistics Program which explores die learning styles of students. We choose two sections of 3° grade of high school (Juan Jimenez Pimentel School) because they were very similar in number of students, learning style, and academic records. Our program was applied in the 3° grade, Section "F" of high school of the mentioned school (which was our "experimental group"), during the 4th bimester 2008. The "control group9 was the 3° grade of high school, Section "E", of the same high school. Their classroom teacher taught them the same subjects in the same period of time.The results of the program fulfilled out expectations. The statistics analysis reveals that after receiving the program of learning styles the students improved their average marks (15.62). And the students who did not receive the program had lower marks (13.88). for all these reasons, we can say that the program of learning styles based on "Neumlinguistics Program" (PNL, for its initials in Spanish) has a significant influence mu the teaching learning process of the English language in the students of the 3"' grade, section "P, of high school, of the Juan Jiménez Pimentel Tarapoto - PERÚ - 2008.